2007
DOI: 10.1007/s00442-007-0770-7
|View full text |Cite
|
Sign up to set email alerts
|

Goose-mediated nutrient enrichment and planktonic grazer control in arctic freshwater ponds

Abstract: A dramatic increase in the breeding population of geese has occurred over the past few decades at Svalbard. This may strongly impact the fragile ecosystems of the Arctic tundra because many of the ultra-oligotrophic freshwater systems experience enrichment from goose feces. We surveyed 21 shallow tundra ponds along a gradient of nutrient enrichment based on exposure to geese. Concentrations of total phosphorus (P) and dissolved inorganic nitrogen (DIN) in the tundra ponds ranged from 2-76 to 2-23 g l ¡1 respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 38 publications
6
57
0
Order By: Relevance
“…Faeces analysis revealed mean PO 4 -P concentrations of 2 mg g -1 dry feces, which is in agreement with the literature data on geese droppings (Van Geest et al, 2007;Ayers et al, 2010). Assuming that a Canada goose daily produces 80 g dry weight of droppings (Scherer et al, 1995), then on average, daily more than 4 kg of droppings are produced around the lake.…”
supporting
confidence: 79%
“…Faeces analysis revealed mean PO 4 -P concentrations of 2 mg g -1 dry feces, which is in agreement with the literature data on geese droppings (Van Geest et al, 2007;Ayers et al, 2010). Assuming that a Canada goose daily produces 80 g dry weight of droppings (Scherer et al, 1995), then on average, daily more than 4 kg of droppings are produced around the lake.…”
supporting
confidence: 79%
“…WAP 20 is very shallow (<0.5 m), has sparse macrophytes, and so the luxuriant benthic mat along the pond bottom has potential to contribute a large fraction of the pond's total primary production. We note that lower-thanexpected phytoplankton chlorophyll a concentrations have been found in other Arctic lakes and ponds and attributed to benthic productivity (e.g., Van Geest et al, 2007;Côté et al, 2010). Moreover, a recent nutrient enrichment experiment that used microcosms containing water from a nearby coastal fen pond, with and without surficial pond sediments and associated benthic algal mat, demonstrated that these ponds rapidly assimilate additions of dissolved inorganic N (nitrate, ammonia) and P (phosphate) when surficial sediments and associated benthic biofilm are present (Eichel et al, 2014).…”
Section: Pond Hydrology and Nutrient Dynamicsmentioning
confidence: 52%
“…For over 20 years, concerns have been mounting about the environmental effects of increased waterfowl populations and how changes in their geographic distribution may alter the structure and function of Arctic and subarctic freshwater ecosystems. Consequences may include eutrophication, changes in nutrient cycling, and destruction of vegetation and available habitat (e.g., Handa et al, 2002;Gregory-Eaves et al, 2004;Lim et al, 2005;Van Geest et al, 2007;Côté et al, 2010;Sun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, polyploid Arctic organisms will have an increased demand for P, which may be constrained by low P content of the food, especially in generally nutrient-poor Arctic ponds (Van Geest et al 2007). Therefore, it can be expected that selection should favour some P-sparing mechanisms, as the animal that develops fastest per unit P used will be favoured in competition (Elser et al 1996;Hessen et al 2008).…”
Section: Discussionmentioning
confidence: 99%